AN ETHNOGRAPHIC STUDY OF THE PERM PRIKAMYE AT THE BEGINNING OF THE XXI CENTURY: EXPEDITIONARY, RESEARCHAND PUBLISHING PROJECTS - Chernikh, A.V. (Perm Federal Research Centre Journal, 2016)
A history of the ethnographic study of the Perm Prikamye and the adjacent territories is investigated by employees of the Sector of Ethnological Studies of the Department of History, Archaeology and Ethnography of the Perm Scientific Centre in the modern period. The directions and theme of the carried out research and their results are analyzed, some promising areas of scientific research are defined.